«A priori forms», «frames», «prototypes» in epistemological theories and speech perception theories - Lobanov, S. D.; Chugaeva, T. N.; Vakhotin, A. A. (Perm Federal Research Centre Journal, 2019)
The article offers an overview of some theories of epistemology, cognitive psychology and perceptual linguistics. The concepts of «a priori forms», «frames», «prototypes», «categorization» are considered and the conclusion follows concerning universal and specific properties of human speech perception.